2D distributions of potential and density mean-values and oscillations in the ECRH and NBI plasmas at the TJ-II stellarator. (1st May 2022) - Melnikov, A V; Eliseev, L G; Barcala, J M; Cappa, A; Chmyga, A A; Drabinskiy, M A; Hidalgo, C; Khabanov, P O; Kharchev, N K; Kozachek, A S; Liniers, M; López-Bruna, D; et al.
Abstract: 2D plasma potential ϕ distribution was measured in the electron cyclotron resonance heating (ECRH) and neutral beam injection (NBI) plasmas of the TJ-II stellarator with the heavy ion beam probe for the whole radial range and wide area of the poloidal angle, and supported by Langmuir probe data at the edge. The whole operation domain for the on-axis ECRH was explored ( n ˉ e = 0.45–0.8 ×10 19 m −3, P EC = 220–470 kW), in addition, NBI plasmas with n ˉ e = 0.9–1.3 × 10 19 m −3 and P NBI = 510 kW were studied. In ECRH plasmas the density ramp-up is accompanied by the evolution of the potential from the bell-like to the Mexican hat profile, while the density profiles were flat or slightly hollow. The potential has the positive peak at the centre, and LFS-HFS (low field—high field sides) and up-down symmetry. Equipotential lines are consistent with vacuum magnetic flux surfaces. In the high-density NBI scenario, the ϕ profile was fully negative with a minimum up to −300 V at the centre, while at low-density ECRH plasma, ϕ has a maximum up to +0.9 kV at the centre. Fluctuations of potential and density are stronger in low-density scenarios and not poloidally symmetric. At the mid-radius (area of the maximum density), root mean square (RMS) of fluctuations were up to ϕ ∼ 15 V at LFS vs ∼20 V at HFS; RMS n e ∼ 2% at LFS vs ∼3% at HFS. In the NBI plasmas with the density rise, the asymmetry decreases and finally vanishing at n ˉ e = 1.2 × 10 19 m −3 . 2D distribution of the NBI-induced Alfvén eigenmodes (AEs) shows asymmetric ballooning structure: contrary to broadband turbulence, AE-associated potential perturbation dominates in the LFS with a factor up to 1.7 respect to the HFS. The electrostatic mode, excited in ECRH plasmas by suprathermal electrons also shows asymmetric structures: density perturbation dominates in the top-bottom direction compared to LFS-HFS direction.